Modified equation for stability computation of round HSS beam–column subject to biaxial moments - Chen, Yiyi; Dong, Baiping (Engineering structures, 2013)
•Existing equations have limitations in stability calculation for HSS beam–column.•Existing equations are over conservative except being unsafe in a few cases.•Modified equations fits physical behavior of HSS beam–column are proposed.•The modified equations have better accuracy and reasonable redundancy.•The modified equations are consistent in beam–column and beam instability behavior. This paper presents the study on equations for stability capacity computation of round hollow structural section (HSS) beam–column subject to axial compression and biaxial moments about two principal axes. By the comparison of numerical results with design interaction formula in major design codes around the world, it is shown that existing design interaction formulas have limitations in stability capacity calculation of HSS beam–column under biaxial moments. Based on theoretical and numerical analysis, an alternative method together with a modified equation is proposed to predict the stability capacity of round HSS beam–columns. The modified equation is verified to be accurate and applicable to various biaxial moment distributions.